The Relationship of Self Efficacy with Cheating Behavior and Implications for Guidance and Counseling Services - Hasnah Karimah; Khairani Khairani; Zadrian Ardi (Jurnal Neo Konseling, 2020)
Today, the phenomenon of student cheating behavior is still often found in the field. One of the factors causing the occurrence of cheating behavior is the low self-confidence of students or the low self-efficacy of students. This study aims to see an overview of students 'cheating behavior, student self-efficacy, and to examine the relationship between self-efficacy and students' cheating behavior. The research method used is descriptive and correlational approaches. The study population was the students of SMA Negeri 3 Padang, amounting to 667 students, with a sample of 250 students who were selected by using stratified random sampling technique. Collecting data using a Likert scale model questionnaire. To see the relationship between the two variables using Pearson Correlation Product Moment. The results of this study indicate: 1) student self-efficacy is in the high category with a frequency of 144 and a percentage of 57.6%, 2) the student's cheating behavior is in the medium category with a frequency of 48% 3) there is a significant negative relationship between self-efficacy and cheating behavior with rxy = - 0.497 and a significant level of 0.000.